2022
DOI: 10.1002/ejoc.202200765
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib‐αVβ3 Integrin Ligand Dual‐Targeting Conjugates towards Precision Treatment of Melanoma

Abstract: Dedicated to Professor Cesare Gennari on the occasion of his 70th birthday.Melanoma is the deadliest form of skin cancer, and more than 150,000 cases are diagnosed every year in Europe. New strategies in treatment approved over the past decade, such as immunotherapy and targeted therapy, have prolonged life expectation even in stage IV melanoma patients. However, due to the increasing incidence of this cancer, the development of new therapeutic strategies remains urgent. Recent studies revealed the combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Tetraphenylethene (TPE) or 1-methyl-1,2,3,4,5-pentaphenylsilole represents such molecules and consists of several conjugated phenyl residues. [130,302] Han et al [130] designed and synthesised a TPE-containing conjugate where the AIE probe is connected via a cathepsin B cleavable Gly-Phe-Leu-Gly peptide to a solubility-enhancing pentaglutamate followed by the Gly-Lys-Gly tripeptide and the integrin addressing DGR (Asp-Gly-Arg) peptide (Table 4.4, entry 10; Nintedanib K562, SSM2c, WM266-4 cells Tyrosine kinase inhibition and blocking angiogenesis [307] Abbreviation: yl =propargylglycine.…”
Section: Tandem Systems As Well As Pdcs and Smdcs Cleaved By Other Hy...mentioning
confidence: 99%
See 2 more Smart Citations
“…Tetraphenylethene (TPE) or 1-methyl-1,2,3,4,5-pentaphenylsilole represents such molecules and consists of several conjugated phenyl residues. [130,302] Han et al [130] designed and synthesised a TPE-containing conjugate where the AIE probe is connected via a cathepsin B cleavable Gly-Phe-Leu-Gly peptide to a solubility-enhancing pentaglutamate followed by the Gly-Lys-Gly tripeptide and the integrin addressing DGR (Asp-Gly-Arg) peptide (Table 4.4, entry 10; Nintedanib K562, SSM2c, WM266-4 cells Tyrosine kinase inhibition and blocking angiogenesis [307] Abbreviation: yl =propargylglycine.…”
Section: Tandem Systems As Well As Pdcs and Smdcs Cleaved By Other Hy...mentioning
confidence: 99%
“…The resulting images revealed that the conjugate reduced angiogenesis more efficiently compared to the unloaded homing device as well as to the combined treatment with sunitinib and the homing device. [200] Bugatti et al [307] used the same linker and RAFT systems as previously described for Sartori et al [200] in combination with the tyrosine kinase inhibitor nintedanib as payload. In addition to two monomeric conjugates a dimeric conjugate, with two c (AmproRGD) units was synthesised and revealed no improved cellular uptake or cell adhesion inhibition abilities in comparison to the monomeric conjugates.…”
Section: Non-cleavable Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytofluorimetric analysis of K562 erythroleukemia cells revealed that they do not express either αvβ6 or αvβ3 integrin receptors (PMID: 35664627); therefore, these cells were used as a negative control (Figure S3A). In addition, we evaluated αvβ6 integrin expression on human melanoma cells (SSM2c, Figure S4A) and murine fibroblasts (L929, Figure S5A), whereas expression of the αvβ3 integrin receptor in these cells had been previously evaluated [35,39]. murine fibroblasts (L929, Figure S5A), whereas expression of the αvβ3 integrin receptor in these cells had been previously evaluated [35,39].…”
Section: Integrin Expressionmentioning
confidence: 99%
“…In addition, we evaluated αvβ6 integrin expression on human melanoma cells (SSM2c, Figure S4A) and murine fibroblasts (L929, Figure S5A), whereas expression of the αvβ3 integrin receptor in these cells had been previously evaluated [35,39]. murine fibroblasts (L929, Figure S5A), whereas expression of the αvβ3 integrin receptor in these cells had been previously evaluated [35,39].…”
Section: Integrin Expressionmentioning
confidence: 99%